Placemaking as a development strategy for the Paal Likupang Beach tourism area - Heince Andre Maahury; Djubir Ruslan Edi Kembuan; Ramadhani Asrar; Desty Rara Retna Kalude; Andi Andre Pratama Putra (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Paal Beach is a tourist attraction that supports the super priority tourist area of Likupang, it needs to get input on the concept of arrangement and development in order to increase its attractiveness as a beach tourism area. This study emphasizes the arrangement and development of the Pall beach tourism area, which has the potential to strengthen the character, impression and meaning of the place. Placemaking approach is used to highlight the uniqueness and strength of a place. This study uses qualitative methods, with descriptive analysis. The results of the study show that, in order to achieve the success of establishing beach tourism, it is necessary to optimize the factors of access and connectivity, comfort and image, lively and interesting activities, and the formation of strong social bonds in forming a sense of place.